The Clinical, Diagnostic, Therapeutic, and Prognostic Characteristics of Brain Metastases in Prostate Cancer: A Systematic Review - Seyyedmohammadsadeq Mirmoeeni; Amirhossein Azari Jafari; Muffaqam Shah; Fateme Salemi; Seyedeh Zohreh Hashemi; Ali Seifi (Prostate Cancer)
Aim. Prostate cancer (PCa) is the second most common nonskin malignancy and the second most common cause of cancer-related deaths in men. The most common site of metastasis in PCa is the axial skeleton which may lead to back pain or pathological fractures. Hematogenous spread to the brain and involvement of the central nervous system (CNS) are a rare occurrence. However, failed androgen deprivation therapy (ADT) may facilitate such a spread resulting in an advanced metastatic stage of PCa, which carries a poor prognosis. Methods. In this systematic review, we searched the PubMed, Scopus, and Web of Science online databases based on the PRISMA guideline and used all the medical subject headings (MeSH) in terms of the following search line: (“Brain Neoplasms” OR “Central Nervous System Neoplasms”) and (“Prostatic Neoplasms” OR “Prostate”). Related studies were identified and reviewed. Results. A total of 59 eligible studies (902 patients) were included in this systematic review. In order to gain a deeper understanding, we extracted and presented the data from included articles based on clinical manifestations, diagnostic methods, therapeutic approaches, and prognostic status of PCa patients having BMs. Conclusion. We have demonstrated the current knowledge regarding the mechanism, clinical manifestations, diagnostic methods, therapeutic approaches, and prognosis of BMs in PCa. These data shed more light on the way to help clinicians and physicians to understand, diagnose, and manage BMs in PCa patients better.